Total harmonic distortion based method for linearity assessment in electrochemical systems in the context of EIS. (20th December 2015) - Giner-Sanz, J.J.; Ortega, E.M.; Pérez-Herranz, V.
Abstract: Electrochemical Impedance Spectroscopy (EIS) is a widely used electrochemical measurement technique that has been used in a great spectrum of fields since it allows deconvolving the individual physic-chemical processes that take place in a given system. Ohm's generalized law, and thus the impedance concept, are only valid if 4 conditions are fulfilled: causality, finiteness, stationarity and linearity. In the case that any of these conditions is not achieved, the obtained impedance spectra will present distortions that may lead to biased or even erroneous results and conclusions. For this reason it is crucial to verify if the 4 conditions are fulfilled, before accepting the results extracted from impedance spectra. In this work, a linearity assessment quantitative method based in the total harmonic distortion (THD) parameter is presented and verified experimentally. The experimental validation of the implemented method showed that the implemented method is able to assess quantitatively the linearity of the system. In addition, it is also able to determine the threshold frequency above which the system will not present significant nonlinear effects even for large perturbation amplitudes. It was observed that the THD method is more sensitive to nonlinear effects than the spectra themselves.